Scale and Skill in Mutual Fund Management: Evidence from Norway - Høiberg, Markus Snøve (SEISENSE Journal of Management, 2020)
Using a sample free of survivorship bias and several risk-adjusted performance benchmarks to identify effects of scale on mutual fund performance in the Norwegian market, I find mixed evidence that both large and small funds underperform as against the middle-sized funds in the period 2005-2018. Controlling for relevant factors in panel data regressions, I find that, on average, performance worsens with an increase in size while giving support to initial findings of nonlinearity. The relationship is most robust after 2013 and seems to be affected by competition in the market as well as fund inflows. I do not find any empirical evidence to support the liquidity hypothesis.